Per-oral cholangioscopy in patients with primary sclerosing cholangitis: a 12-month follow-up study - Mohamed, Rachid; Tejaswi, Sooraj; Aabakken, Lars; Ponsioen, Cyriel Y; Bowlus, Christopher L; Adler, Douglas G; Forbes, Nauzer; Paulsen, Vemund; Voermans, Rogier P.; Urayama, Shiro; Peetermans, Joyce; Rousseau, Matthew J; Eksteen, Bertus (Endoscopy International Open, 2024)
Background and study aims Patients with primary sclerosing cholangitis (PSC) have a 9% to 20% lifetime incidence of cholangiocarcinoma (CCA). Per-oral cholangioscopy (POCS) added to endoscopic retrograde cholangiography (ERC) could potentially improve detection of CCA occurrence. We prospectively assessed POCS identification of 12-month CCA incidence in PSC patients undergoing ERC.Patients and methods Consecutive patients with PSC, an indication for ERC, and no prior liver transplantation were enrolled. During the index procedure, POCS preceded planned therapeutic maneuvers. The primary endpoint was ability for POCS visualization with POCS-guided biopsy to identify CCA during 12-month follow-up. Secondary endpoints included ability of ERC/cytology to identify CCA, repeat ERC, liver transplantation, and serious adverse events (SAEs).Results Of 42 patients enrolled, 36 with successful cholangioscope advancement were analyzed. Patients had a mean age 43.5±15.6 years and 61% were male. Three patients diagnosed with CCA had POCS visualization impressions of benign/suspicious/suspicious, and respective POCS-guided biopsy findings of suspicious/positive/suspicious for malignancy at the index procedure. The three CCA cases had ERC visualization impressions of benign/benign/suspicious, and respective cytology findings of atypical/atypical/suspicious for malignancy. No additional patients were diagnosed with CCA during median 11.5-month follow-up. Twenty-three repeat ERCs (5 including POCS) were performed in 14 patients. Five patients had liver transplantation, one after CCA diagnosis and four after benign cytology at the index procedure. Three patients (7.1%) had post-ERC pancreatitis. No SAEs were POCS-related.Conclusions In PSC patients, POCS visualization/biopsy and ERC/cytology each identified three cases of CCA. Some patients had a repeat procedure and none experienced POCS-related SAEs.
Keywords: Cholangioscopy; Pancreatobiliary (ERCP/PTCD); Diagnostic ERC; Endoscopy Upper GI Tract; Malignant strictures